PEMBANGUNAN MANUSIA PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2005)
There is a gap of development achievement in Indonesia. At least it can be observed from human development index (HDI) in the period of 1996- 2002 which show a significant different across provinces. Among provinces in Java, Yogyakarta sit in the second position after Jakarta in the year of 1996 and 1999, but it became third rank in the year of2002. As it was in other provinces, the value of the index is still lower in 2002 compared to 1996, but higher than in 1999. It means the economic crisis which hit the country affect the human development a lot. In the same time among the district in the Yogyakarta province, the gap of HDI also appeared between the District of Gunung Kidul which the rank was 140 and the city of Yogyakarta which the rank was Q in 2002. Even the gap was higher in 1996 and 1999 because the rank of Gunung Kidul is 187 and 1965 respectively while it was 5 and 2 for the city of Yogyakarta. Gunung Kidul is also the area which was the most hit by the crisis as can be seen from the sharp decline in people's purchasing power. However this area experience faster recovery shown by the higher increase of purchasing power than other districts.